The Ten Most Beautiful Experiments - George Johnson (Alfred A. Knopf, 2008)
The ten most fascinating experiments in the history of science--moments when a curious soul posed a particularly eloquent question to nature and received a crisp, unambiguous reply. Johnson takes us to those times when the world seemed filled with mysterious forces, when scientists were dazzled by light, by electricity, and by the beating of the hearts they laid bare on the dissecting table. For all of them, diligence was rewarded. In an instant, confusion was swept aside and something new about nature leaped into view. In bringing us these stories, Johnson restores some of the romance to science, reminding us of the existential excitement of a single soul staring down the unknown.--From publisher description.